2016
DOI: 10.1017/s1368980016001701
|View full text |Cite
|
Sign up to set email alerts
|

Social influences on eating and physical activity behaviours of urban, minority youths

Abstract: Objective Social relationships can impact youths’ eating and physical activity behaviours; however, the best strategies for intervening in the social environment are unknown. The objectives of the present study were to provide in-depth information on the social roles that youths’ parents and friends play related to eating and physical activity behaviours and to explore the impact of other social relationships on youths’ eating and physical activity behaviours. Design Convergent parallel mixed-methods design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Although participants reported increased availability of healthier food items due to parental food acquisition and positive role modeling making it easier to eat healthier food items at home, some participants in Prong 2 noted that parents often provide negative role modeling by providing high-fat, high-sugar items in the home that are tempting, particularly when parents are consuming them frequently. These findings support previous research conducted by Anderson Steeves et al [54].…”
Section: Discussionsupporting
confidence: 93%
“…Although participants reported increased availability of healthier food items due to parental food acquisition and positive role modeling making it easier to eat healthier food items at home, some participants in Prong 2 noted that parents often provide negative role modeling by providing high-fat, high-sugar items in the home that are tempting, particularly when parents are consuming them frequently. These findings support previous research conducted by Anderson Steeves et al [54].…”
Section: Discussionsupporting
confidence: 93%
“…A previous systematic review, for example, revealed racial/ethnic differences in fruit and vegetable intake and pointed to the need to consider various influences on intake when designing dietary interventions for low-income youth [37]. Another study in low-income African-American adolescents showed that specific social relationships have specific roles; for example, aunts provided exposure to novel food experiences [38]. In conducting future studies in this demographic, examination of all the contextual factors shaping adolescent eating will be important.…”
Section: Discussionmentioning
confidence: 99%
“…younger and male [ 62 ], although there were no differences by weight status or education level. Moreover, insights from the qualitative data suggested that future DCEs in young adults should consider the role of social influences and cooking skills, which are known determinants of food choice [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%